And Yet they Co-Move! Public Capital and Productivity in OECD: A Panel Cointegration Analysis with Cross-Section Dependence - Anna Bottaso; Carolina Castagnetti; Maurizio Conti (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2011)
In this paper we add to the debate on the public capital - productivity link by exploiting very recent developments in the panel time series literature that take into account cross sectional correlation in non-stationary panels. In particular we evaluate the productive effect of public capital by estimating various production functions for a panel of 21 OECD countries over the period 1975-2002. We find strong evidence of common factors that drive the cointegration relationship among variables; moreover, our results suggest a public capital elasticity of GDP in the range 0.05-0.15, depending on model specification. Results are robust to the evidence of spillovers from public capital investments in other countries and to controlling for other productivity determinants like human capital, the stock of patents and R&D capital.
Keywords: C33; C15; H54; O47; 330; Public capital; Productivity; Panel Cointegration; Cross-section Dependence